Identification, Distribution and Abundance of Scale Insect Associate with Several Clones of Durian (Durio zibethinus Merr.) - Affandi Affandi; Dhasa Lististio; Panca Jarot Santoso; Ellina Mansyah; Dewi Sartiami (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
Durian contributes a high economic value in agribusiness of horticultural product. However, recently the attack of scale insect has devastated most of pre-production trees in Indonesia. A research with objective to know the basic information about the correct species, distribution and population abundance was done at Aripan Research Station of Indonesian Tropical Fruits Research Institute from July to August 2018. A proper identification and observation method were used to know the species identity, distribution and abundance of the insect. Biotic and abiotic factors in each clone such as nutrients content, tree morphological characteristic, light intensity, temperature and relative humidity under canopy were analysed. The result showed that Aulacaspis vitis Green was a scale insect identified associating with durian leaves. Clone Bintana and Sikapal were the most and the less preferred with the intensity of damage was 88.60 % and 38.30 %, respectively. Nutrient content especially nitrogen and water as well as canopy morphology were simultaneously the most contributed in the preference of a certain clone. The pest was preferred to clump in the East cardinal direction and no significant difference between upper and lower part of the tree including within and outside of the canopy.